Analisis Life Cycle Cost (LCC) pada Pembangunan Gedung Asrama Putri di Malang - Sandi Wahyudiono; Faris Rizal Andardi (Jurnal Konstruksi, 2026)
This study aims to analyze the total life cycle cost of the construction of the Sumbersari Female Dormitory Building in Malang using the Life Cycle Cost (LCC) method. The analysis covers three cost components—initial cost, operational cost, and maintenance cost—over a 30-year horizon with a discount rate of 6%. Initial cost data were obtained from the project budget plan, while operational and maintenance costs were determined based on a percentage of the initial cost and a periodic maintenance schedule. This study introduces a new aspect compared to similar LCC studies of building projects by presenting the Equivalent Annual Cost (EAC) as an annual value to support long-term budgeting, as well as analyzing the contribution of each cost component to facility management efficiency for dormitory-type buildings. The results show that the total LCC (NPV) amounts to IDR 3,415,850,000, with cost composition consisting of 75.8% initial cost, 20.9% operational cost, and 3.3% maintenance cost. The EAC value reaches IDR 248,158,000 per year, or approximately IDR 128,000/m² per year. These findings indicate that although maintenance costs account for a relatively small proportion, scheduled maintenance plays an important role in controlling increases in operational costs and maintaining facility performance in the long term. The results of this study can serve as a basis for budgeting and more efficient maintenance strategies for educational facilities.